1999
DOI: 10.1046/j.1365-2982.1999.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Cortical activation during oesophageal stimulation: a neuromagnetic study

Abstract: We investigated the neuromagnetic responses to mechanical stimulation of the oesophagus. In six healthy right-handed volunteers (mean age 31.6 years) the proximal and distal oesophagus were stimulated by electronically controlled pump-inflation of a silicone balloon once every 4.5-5.5 sec (dwell time 145 msec). The balloon volume was adjusted to induce different sensation levels (i) just above threshold of perception, (ii) strong sensation and (iii) painful sensation. Evoked magnetic brain responses were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 43 publications
(87 reference statements)
1
4
0
Order By: Relevance
“…Recently, the technique has been applied to a number of clinical chronic pain disorders, including fibromyalgia [40,41], chronic low back pain [42,43], and neuropathic pain [44–48], in an effort to define central mechanisms that may contribute to subjective pain symptoms in those disorders. The findings with fMRI parallel other advances in the imaging of brain regions involved in central pain processing that have been made with PET [49–55] and magnetoencephalopathy [36,49,56–62].…”
Section: Social Influencessupporting
confidence: 56%
“…Recently, the technique has been applied to a number of clinical chronic pain disorders, including fibromyalgia [40,41], chronic low back pain [42,43], and neuropathic pain [44–48], in an effort to define central mechanisms that may contribute to subjective pain symptoms in those disorders. The findings with fMRI parallel other advances in the imaging of brain regions involved in central pain processing that have been made with PET [49–55] and magnetoencephalopathy [36,49,56–62].…”
Section: Social Influencessupporting
confidence: 56%
“…Previous EEG studies also found evidence for early bilateral insular activation. 8 32 In common with the MEG studies of the oesophagus, 30 31 36 we found insular activation shortly before or simultaneously with activation of the sensory cortex in most subjects. This is in agreement with animal studies of anatomical data, suggesting that the insula has an important function for integrating visceral sensory and motor activity together with limbic integration.…”
Section: Methodological Considerationsmentioning
confidence: 60%
“…The first MEG based studies found evidence for bilateral activation of the primary and secondary sensory cortex, insula, cingulate, and prefrontal cortex. [28][29][30][31] Previous EEG studies using brain mapping and dipole source modelling of ERPs to mechanical stimulation of the oesophagus found evidence of dipoles close to the cingulate gyrus and insula. [32][33][34] We have modelled the electrical dipoles to painful electrical stimulation of the sigmoid colon.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“… 31 As the primary somatosensory cortex only receives spinal afferents, where as the insular receives both vagal and spinal afferents, it is likely that oesophageal CEP is mediated by both vagal and spinal afferents and not solely vagal as has been suggested. Furthermore, recent MEG studies 32 , 33 suggest that oesophageal electrical stimulation and balloon distension activate similar regions of the cortex; therefore it is likely that CEP generated by both methods of stimulation are mediated via the same pathways. At present it is not possible to say precisely which fibres are being stimulated using our parameters.…”
Section: Discussionmentioning
confidence: 99%